2016
DOI: 10.1542/hpeds.2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Potentially Preventable Pediatric Admissions Vary by Diagnosis: Findings From a Large State

Abstract: A B S T R A C T OBJECTIVES:The objective of this study was to determine characteristics associated with potentially CONCLUSIONS: Potentially preventable admissions represent a high burden of time and costs for the pediatric population, but strategies to reduce them should be tailored to each diagnosis because the associated factors are not uniform across all potentially preventable admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Younger children were more likely to be hospitalized for an ACSC and for dehydration. This finding has already been reported and in these studies younger children were also more likely to come to the hospital without a referral[6,19]. It may be hypothesized that admitting doctors are more prone to hospitalize when the individual is an infant or young toddler, for which some clinical conditions may be more dangerous, such as, for example, a febrile neonate being at higher risk for serious bacterial infections than older children.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Younger children were more likely to be hospitalized for an ACSC and for dehydration. This finding has already been reported and in these studies younger children were also more likely to come to the hospital without a referral[6,19]. It may be hypothesized that admitting doctors are more prone to hospitalize when the individual is an infant or young toddler, for which some clinical conditions may be more dangerous, such as, for example, a febrile neonate being at higher risk for serious bacterial infections than older children.…”
Section: Discussionsupporting
confidence: 66%
“…Although ACSCs have been less used in the pediatric population, the results of this study show the usefulness of these conditions as indicators of the burden of preventable hospitalizations. In this study context 10.5% of all pediatric hospitalizations were preventable; in previous studies performed in Europe and USA using the same definition of preventable hospitalization described in this study, prevalence of these conditions showed variable results ranging from 5% to 40%[6,7,19]. Although high, our prevalence is one of the lowest when compared with the data reported in other studies[3,6,7].…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…14 Studies in pediatrics, however, have shown lower overall admission and 30-day readmission rates and potentially less preventability. [15][16][17] Hence, the 30-day readmission rate may have limited utility as a quality metric in the pediatric population.…”
mentioning
confidence: 99%